Shift work sleep disorder in nurses: a concept analysis - Liangmeng Yu; Huiyue Zhou; Jiamei Li; Xiaoling Yu (BMC Nursing)
Abstract Aim This study seeks to elucidate the concept of shift work sleep disorder (SWSD) among nurses, thereby offering a comprehensive understanding that can inform future research and practical interventions. Methods Walker and Avant’s concept analysis method was employed to guide the study. A systematic literature review was conducted utilizing various databases, including PubMed, Embase, EBSCO, Web of Science, CNKI, WanFang, and Sino Med. The inclusion criteria were specifically designed to focus on studies that define SWSD, along with its attributes, antecedents, consequences, and assessment tools relevant to nursing professionals. Results The analysis identified four key attributes of SWSD: internal/external circadian rhythm imbalance, impaired sleep, multidimensional health problems, and dynamic changes in symptoms. Antecedents include individual factors like personal health, lifestyle, family support, shift patterns, work environment, and other organizational factors. Consequences of SWSD encompass physiological health issues, mental health challenges, impaired social adaptability, and decreased nursing performance. Conclusion SWSD has a significant impact on the health and performance of nurses. Understanding its attributes, antecedents, and consequences is crucial for developing targeted interventions. Enhancing sleep hygiene, fostering supportive work environments, and implementing appropriate shift scheduling can help mitigate the adverse effects associated with SWSD.